Intestinal Parasites and Risk factors among inmates in Umuahia Abia State, Nigeria - Queen Ozioma Lawrence; Anthonia Nnenna Chuks Amadi; Chinenye Okosa; Eberejah, Juliet John; Nsikakabasi Charles Ukpong; Prisca Chimerebere4 Aririguzo (Hasanuddin University, 2022)
Human intestinal parasites are among the most common infectious diseases worldwide. This study was conducted to determine intestinal parasites prevalence and risk factors in the study area. A total of 350 consented inmates aged 18->60 years participated in the study. Stool samples were screened using wet preparation and formol ether concentration method. An overall prevalence of 48.8% was recorded for intestinal parasite, which was significantly (p< 0.05) high among females. Five species of intestinal parasite were identified. The most common identified was hookworm (95, 33.5%), while the least was Trichuris trichiuria (33, 11.6%). Age group 51-60 years recorded the highest infection (63.33%) among the males, while age group 18-20 years had the least (25.0%). Age groups 51-60 and >60 years recorded 100% infections among the females. Of the 171 infections recorded, 97(56.7%) had single infection, while 74(43.3%) had multiple infections. Questionnaire analysis showed that inmates who have been in the prison for years were more parasitized. Inmates who deworm monthly, yearly and not at all accounted for 64.2%, 78.7% and 39.2% infections respectively which was significant (p< 0.05). The study revealed the prevalence of intestinal parasitic infections in the inmates. Improved healthcare and awareness is highly recommended inside the facility.